TEKNOLOGI TEPAT GUNA MENDUKUNG PENGEMBANGAN SAPI LOKAL PESISIR SUMATERA BARAT - Rahmi Wahyuni; R. A. Dewi (Jurnal Penelitian dan Pengembangan Pertanian, 2018)
The few last decades the growth of Pesisir Cattle has stagnated due to the decline in the genetic quality. The an proper of culturing management was respected as the main problem in the developing Pesisir Cattle, with the result that the demand elasticity was not comparable with growth. The interoduction of approviate management and technology based on the local resource was considered capable to improve the Pesisir Cattle productivity. This research is try to examine the approvible technology based to local resource to support the development of Pesisir Local Cattle at west Sumatera. The several management and technology innovation can be appled to improve the culturing management, namely: (1) reproductive management by applying artificial Insemination marriage system and use the of superior male; (2) Feed technology through the use of derived process technology such as palm leaf silage depend on local resouces and development of leguminous plants cultivation that it rich in protein; (3) Technology innovation of group cage management such as Grati to breeding as well as to fattening of catle; (4) Integrated farming system according to local culture; (5) Applying of sustainable production system, in which farmers are motivated to work on two forms of livestock business namely fattening and breeding as well; (6) Developing a livestock breeding business system to accelerate the changing pattern of maintenance from an extensive system to an intensive system.Keywords: Technology, Pesisir cattle, West Sumatera AbstrakDalam beberapa dekade terakhir, pertumbuhan sapi pesisir di Sumatera Barat mengalami stagnasi akibat menurunnya kualitas genetik ternak. Manajemen pemeliharaan yang kurang baik merupakan masalah utama dalam pengembangan sapi pesisir sehingga elastisitas permintaan tidak sebanding dengan pertumbuhan. Introduksi manajemen dan teknologi tepat guna berbasis sumber daya lokal dinilai mampu meningkatkan produktivitas sapi pesisir. Tulisan ini membahas teknologi tepat guna berbasis sumber daya lokal mendukung pengembangan sapi lokal pesisir Sumatera Barat. Inovasi manajemen dan teknologi yang dapat diterapkan untuk memperbaiki pola pemeliharaan sapi pesisir antara lain: (1) manajemen reproduksi dengan mengaplikasikan teknologi inseminasi buatan (IB) dan penggunaan pejantan unggul; (2) teknologi pakan dengan memanfaatkan limbah tanaman seperti silase pelepah daun sawit, bergantung pada sumber daya lokal dan pengembangan tanaman leguminosa yang kaya protein; (3) inovasi teknologi dan manajemen pengelolaan kandang kelompok seperti “Kandang Kelompok Grati”, baik untuk tujuan pembibitan maupun penggemukan ternak; (4) pertanian terpadu sesuai dengan budaya setempat; (5) sistem produksi berkelanjutan, dalam hal ini peternak dimotivasi untuk mengembangkan dua bentuk usaha ternak sekaligus, yakni penggemukan dan pembibitan; (6) pemeliharaan ternak dengan sistem gaduhan untuk percepatan perubahan pola pemeliharaan dari ekstensif ke intensif.Kata kunci: Teknologi, sapi pesisir, Sumatera Barat.